Heterogeneity of subclinical autistic traits among parents of children with autism spectrum disorder: Identifying the broader autism phenotype with a data-driven method - AYDIN, AYDAN (WILEY, 2017)
Clinical diagnosis of autism spectrum disorder (ASD) can be conceptualized as the extreme end of the distribution of subclinical autistic traits related to genetic susceptibility factors (broad autism phenotype (BAP)) in the general population. Subclinical autistic traits are significantly more common among unaffected first-degree relatives of probands with autism. However, there is a significant heterogeneity of autistic traits in family members of individuals with ASD and severity of autistic traits are not significantly different from controls in the majority of these relatives. The current study investigated the heterogeneity of autistic traits using latent class analysis (LCA) of the Autism Spectrum Quotient (AQ) ratings of 673 parents of children with ASD and 147 parents of typically developing children. Two distinct subgroups, including a low-scoring and a high-scorer (BAP) groups, were found. In comparison to control parents, a significantly larger proportion (21.1% vs. 7.5%) of parents of ASD were members of BAP group. Communication subscale made a distinctive contribution to the separation of high and low-scoring groups (d=2.77). Further studies investigating neurobiological and genetic biomarkers and stability of these two subgroups over time are important for understanding the nature of autistic traits in the general population. Autism Res2017, 10: 321-326. (c) 2016 International Society for Autism Research, Wiley Periodicals, Inc.
Keywords: autistic traits; autism-spectrum questionnaire; latent class analysis; broader autism phenotype; MULTIPLE-INCIDENCE; TURKISH VERSION; LANGUAGE IMPAIRMENT; FAMILY-HISTORY; QUOTIENT; SIBLINGS; FEATURES; PROBANDS; TWIN